IMPROVING BUSINESS PERFORMANCE USING FINANCIAL PLANNING TOWARD PLUS-SIZE FASHION BUSINESS - Afti Insani Nurmahmudiyah; Raden Aswin Rahadi; Atika Irawan (JAF (Journal of Accounting and Finance), 2020)
Indonesian as one of the countries that accept globalization. Indonesian economic development plans make the development of creative industries like one of the main priorities. The problem arises that some industry players cannot harness the capital well as the SME's company in the modern era's we need to manage the financial well and minimalized the cost. Avant Grande is a Bandung company that is running a business in customizing denim pants. Avant Grande implement the system of business made by order and ready stock. We found that in comparison with current performance with past performance, using ratios allows us to analyse the progress of the firm. The firm’s progress is “Poor” because from 2017 to 2018, there was a decreasing ratio value. After using DuPont System of Analysis to find the root cause, the researcher needs to dissect the net profit margin. From the discussion and root cause finding, to make Avant Grande best in performance in business, Avant Grande need to do the planning. For the solution, the Avant Grande business is needed to do Long-term Financial Planning.